Classification of the discus throw technique - Maeda, K.; Kato, T.; Mizushima, J.; Ohyama-Byun, K. (ISBS Proceedings Archive (Michigan), 2022)
The purpose of this study is to classify discus throwers based on the velocity components at release and to investigate their throwing biomechanics. Forty-six male discus throwers were classified into 2 groups through cluster analysis. Twenty-two throwers were classified into a horizontal dominant group, while the remaining 24 throwers were classified into a vertical dominant group. There were no significant differences in the throwing distance and resultant release velocity between the groups. The right leg angle at release and the displacement of the centre of gravity (vertical direction) were significantly greater in vertical dominant group. These results indicated the horizontal dominant group drove their right leg forward to increase the horizontal velocity, while the vertical dominant group lifted their body upward direction to increase the vertical velocity.